Notes on Gàlì (Miltu), a Moribund Chadic Language (Republic of Chad) - Jungraithmayr, Herrmann; Peust, Carsten (Folia Orientalia, 2026)
A short description of Gali, an East Chadic language, based on field notes taken in 1972.